2019
DOI: 10.1177/0898010119880116
|View full text |Cite
|
Sign up to set email alerts
|

The Lived Experiences of Folklore Healing Practices as a Health Patterning Modality

Abstract: Purpose: The purpose of the study is to understand the meaning of folklore as a health patterning modality and to uncover its unique characteristics in the life-health process. Design: Hermeneutic phenomenological. Method: Max van Manen’s methodology was used for this study. The sample was selected from the Afro-Caribbean American community in the United States. The criterion for selection was that participants used folklore healing practices for health and well-being on an ongoing basis. In-depth interviews w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(53 reference statements)
0
3
1
Order By: Relevance
“…This research also makes a theoretical contribution to existing literature on how folk literature can be used as therapy to ensure healthy ageing. Unlike other researchers' findings (Joseph 2019;Hufford 1998), our findings relate to the role of Sindhi folk literature in enhancing the psychological, social, and spiritual wellbeing of senior citizens in Pakistan's Sindh province. We suggest that the public health sector in Sindh should hire the services of such senior citizens and encourage such conversations in informal settings (guest houses, open air theatres) and formal settings (clinics, educational institutions) so that the spiritual, psychological, and social health of everyone can be improved.…”
Section: A Critical Summationcontrasting
confidence: 96%
See 2 more Smart Citations
“…This research also makes a theoretical contribution to existing literature on how folk literature can be used as therapy to ensure healthy ageing. Unlike other researchers' findings (Joseph 2019;Hufford 1998), our findings relate to the role of Sindhi folk literature in enhancing the psychological, social, and spiritual wellbeing of senior citizens in Pakistan's Sindh province. We suggest that the public health sector in Sindh should hire the services of such senior citizens and encourage such conversations in informal settings (guest houses, open air theatres) and formal settings (clinics, educational institutions) so that the spiritual, psychological, and social health of everyone can be improved.…”
Section: A Critical Summationcontrasting
confidence: 96%
“…Many researchers have already identified the role of folklore in developing healthy ageing (Joseph 2019;Hufford 1998;Newton 2019;Puglisi et al 2017). Joseph's (2019) hermeneutic, phenomenological, and qualitative study showed how the Afro-Caribbean people use folklore practices as a health patterning modality.…”
Section: Folk Literature and Healthy Ageingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the World Health Organization (2008), folklore is defined as the knowledge, skills, and practices based on the beliefs and experiences of a society. (1) The origin of Indian medicines are shrouded in myths. It can certainly be valuable source of clues to the usefulness of plants and the kinds of relationships that human communities have had with them.…”
Section: Introductionmentioning
confidence: 99%